Arthropod Pests of Horticultural Crops in Tropical Asia - Muniappan, Rangaswamy (CABI, 2014)
The world’s population surpassed 7 billion in late 2011, with predictions that it will exceed 9 billion by 2050. Demand for food from cereal and horticultural crops is expected to grow accordingly. As many Asian countries become more developed, the demand for food from horticultural crops is expected to increase even more. Agriculture will be required to meet this food demand with less land, less water, and less labor. Although staple food is provided by the two main cereals, rice and wheat, food from horticultural crops such as beans, vegetables, and fruits is also signiﬁ cant for humans. The huge variety of food produced from horticultural crops will provide not only diversity in taste but also sources of nutrients, minerals, and vitamins for humankind to enjoy healthy food. Nonetheless, insect pests are constant threats to horticultural crop production. Insects are the principal causes of yield losses in cabbage, mango, and bean crops. In Asia, growers generally rely on insecticides to avoid crop loss. In the past 5 years, insecticide usage in many developing countries has escalated and misuse is becoming more abundant. Pesticide residues in horticultural crops are becoming a deep concern. For growers to manage their crops properly with a minimal use of pesticides, it is vitally important to be able to diagnose pest problems. Similarly, for crop protection technicians and educators to be able to advise growers and teach, they need to identify insect pests, assess the damage they cause, and identify the related natural enemies. This book, Arthropod Pests of Horticultural Crops in Tropical Asia, is an excellent reference for researchers, extension personnel, and university students. The text provides detailed descriptions of pests, their taxonomy, Latin and common names, their host ranges, the kinds of damage they cause, and their natural enemies. Most relevant of all is the excellent photography by the authors of the pest species and damage for readers to view. The photographs are from the authors’ decades-old photo collections and many patient hours spent in capturing the images. I am very glad that the authors are sharing their valuable photos with the world. This book will be an important contribution to science, research, and the implementation of integrated pest management of horticultural crops in Asia.